GCT-31. DIAGNOSTIC CAPABILITY OF CSF-PLAP ON INTRACRANIAL GERM CELL TUMOR. (4th December 2020) - Okamoto, Michinari; Yamaguchi, Shigeru; Ishi, Yukitomo; Motegi, Hiroaki; Terashita, Yukayo; Hirabayashi, Shinsuke; Sugiyama, Minako; Cho, Yuko; Iguchi, Akihiro; Manabe, Atushi; Houkin, Kiyohiro
Abstract: BACKGROUND: Since the majority of intracranial germ cell tumor(GCT) is sensitive for chemoradiation, biopsy specimens are usually tiny and not enough for accurate pathological diagnosis. To supply complementary diagnostic information, a-fetoprotein or human chorionic gonadotropin-b are important biomarkers. Recently CSF-placental alkaline-phosphatase(PLAP) is also reported as an additional biomarker in intracranial GCT. This study's purpose is to evaluate the significance of CSF-PLAP. METHODS: CSF-PLAP was obtained from the patients with the intraventricular and periventricular tumor before any adjuvant therapy. Definitive diagnoses were made by histopathological information and/or their clinical courses; GCT(germinoma or non-germinomatous GCT(NGGCT)) or other tumors. In GCT, the relationship between CSF-PLAP and tumor reduction volume was evaluated. Tumor volumes were calculated on gadolinium-enhanced T1-weighted magnetic resonance imaging before and after initial chemoradiotherapy. RESULTS: Between 2005 and 2019, 42 patients were studied: 24 with GCT and 18 with others. CSF-PLAP value in patients with GCT was significantly higher than those with others: the Specificity was 88% and the sensitivity was 95% at the cutoff value of 8.0 pg/ml. For GCT patients, CSF-PLAP value tended to be higher in germinoma(n=12, mean 4756 pg/ml), compared to the value in NGGCT(n=7, mean 332 pg/ml), although there was no statistical difference. There was a significant positive correlation between initial CSF-PLAP value and tumor reduction volume. CONCLUSION: CSF-PLAP is a useful tumor marker for GCT differentiating from the other tumors located in intraventricular and periventricular region and CSF-PLAP value might correlate with the volume of germinomatous component of the tumor.